Basic calcium phosphate crystals and osteoarthritis pathogenesis: novel pathways and potential targets. Issue 2 (March 2016) - Stack, John; McCarthy, Geraldine
Abstract : Purpose of review: Basic calcium phosphate (BCP) crystals have long been associated with the pathogenesis of osteoarthritis. As our knowledge concerning BCP crystals in osteoarthritis expands, so does the potential to develop targeted therapies. The present review discusses recent advances in this field and attempts to summarize our current understanding regarding the role of BCP crystals in osteoarthritis pathogenesis. Recent findings: BCP crystals injected into the knees of mice induce osteoarthritis-like changes, further evidence of their pathogenic properties. Interleukin-6 has emerged as a key cytokine involved in BCP crystal-induced inflammation that could represent a potential therapeutic target. The role of BCP crystal-induced osteoclastogenesis has also recently been explored and may also hold the key to future targeted therapies. Although tools to detect BCP crystals remain limited, dual energy computerized tomography scanning has emerged as a useful noninvasive means of quantifying intra-articular calcium crystal deposition. Summary: BCP crystals can activate a number of inflammatory pathways which in turn may lead to cartilage degradation and osteoarthritis. Understanding of these pathways may ultimately yield targeted therapies for osteoarthritis, for which none currently exists.